Clinical and Radiological Changes of Ankle in Knee Osteoarthritis With Varus After Total Knee Arthroplasty: A Systematic Review - Feng, Zhiwei; Ma, Ming; Wang, Yaobin; Yang, Chenfei; Liu, Zhongcheng; Xia, Yayi (Frontiers in Surgery, 2021)
Background: Arthritis with severe varus deformity remains a challenge in total knee arthroplasty (TKA). Until recently, surgeons aimed at a neutral lower limb alignment when performing a TKA. However, the impact of TKA on the ankle joint has been ignored. Therefore, we conducted a systematic review to assess the clinical and radiological changes in the ankle joint after TKA on knees with severe varus deformity. Methods: A systematic search was conducted in four English (PubMed, Embase, Cochrane Library, and Web of Science) and four Chinese (CBM, VIP, CNKI, and Wan Fang Database) databases. Screening of literature and extraction of data were independently performed by two researchers. The modified methodological index for non-randomized studies (MINORS) was used to assess the quality. Results: A total of eight studies were eligible, namely, four prospective and four retrospective studies. TKA resulted in a negative clinical effect in the ankle joint in patients with ankle osteoarthritis. Seven studies reported changes in the mechanical tibiofemoral angle, and four studies reported radiological changes in the hindfoot. The mean score of the MINORS was 9.8 out of eight (9–11). Conclusion: As a result of the correction of the knee osteoarthritis with severe varus deformity following mechanically aligned TKA, the radiological malalignment of the ankle joint was improved. However, some patients experience increased ankle pain after undergoing TKA, especially, if there was a residual knee varus deformity, a stiff hindfoot with varus deformity, or ankle arthritis.